Transforming Landscapes: How ODR reshaping the prospect of dispute settlement in a connected world - Ruslijanto, Patricia Audrey (UI Scholars Hub, 2018)
The existence of law and culture has bring significant forces to human life, since them both shaping and influencing the emergence of values and norms in communities and societies. The restless development of human history has forged law in dynamic relation with culture, resulted in changing laws, values and practices. Beyond politics, present life is also bringing fresh challenges for law and culture globally, such as: the increased use of technology in law and human life. One of the big leap issue is the changing in the culture of trade, which shifted to non-face-to face or e commerce, which offer easiness and practicality in conduct trade regardless the non-barrier border. Indeed, there is still a lack of effective legal regimes and processes capable to meet the needs of globalization. The increased possibilities to access information, to form online relationships, and to conclude online transactions have introduced a new dimension of legal conflicts, which is electronic disputes. Regarding this issue, the needs of effective dispute settlement, which is “fitting to the forum”, is necessary, and online dispute resolution (ODR) is the answer. Therefore this paper aims to find how ODR reshaping the prospect of dispute settlement and what obstacle may be faced by the implementation of ODR. The method use in this paper is juridical normative with conceptual approach, statute approach and comparative approach. The result of this paper show that ODR able to reshape the prospect of dispute settlement, since it may offer fairness by providing transparent system of negotiation, trust in content offer by ODR system and security develop in ODR system in the process of dispute settlement. Meanwhile, there are also obstacles that may face by ODR, which are technology issue and local culture issue, which means the acceptance of ODR practice in society, especially when applied to developing country.